Perlindungan Konsumen Pada Transaksi Jual Beli Online - Elfirda Ade Putri (Jurnal Pengabdian kepada Masyarakat UBJ, 2023)
A business actor is any individual or business entity, whether in the form of a legal entity or not a legal entity established and domiciled or conducting activities within the jurisdiction of the Republic of Indonesia, either alone or jointly through an agreement to carry out business activities in various economic fields. As it has been stated that nowadays, many business actors are starting to offer their business activities through online mechanisms, on the other hand, consumers also welcome this online transaction model, so its development online transactions appear to be growing. In connection with this phenomenon, it is important to study and socialize the legal basis of online transactions, especially in the context of consumer protection. The method used is the dissemination of socialization materials and the legal basis for consumer protection and efforts to resolve consumer disputes in buying and selling online. The results of the implementation of the community are able to understand that sellers and buyers have rights and obligations, sellers have responsibilities if consumer rights are not fulfilled, and efforts to resolve disputes with litigation effort and non-litigation effort.